Neuronal regulation of innate lymphoid cell responses. (June 2022) - Yano, Hiroshi; Artis, David
Abstract : The immune system and the peripheral nervous system are distributed throughout the body and surveil vital organs utilizing various sensory mechanisms. Previous studies have demonstrated that tissue-resident innate lymphoid cells (ILCs) and neurons are heavily enriched in the body's barrier surfaces, where it is critical to detect and rapidly adapt to the changes in dietary, microbial and other environmental stimuli. However, our understanding of how these two sensory systems cooperatively integrate these diverse signals to orchestrate host responses remains incomplete. Recent research has provided insights into how neurotrophic and neuronally derived factors regulate the functions of ILCs, establishing the neuro–ILC axis as a crucial component of broader neuro–immune interactions. Further, neurons express receptors for many cytokines produced by ILCs, opening the possibility for bidirectional neuro–immune interactions in regulating tissue homeostasis and inflammation. This review highlights recent advances in the cellular and molecular mechanisms of neuro–ILC interactions and their potential therapeutic implications. Highlights: Innate lymphoid cells (ILCs) colocalize with tissue-innervating peripheral neurons. Neurotransmitters and neuropeptides directly regulate ILC responses. Neuronal responses can be regulated by inflammatory cytokines. Neuro–ILC interactions are potential therapeutic targets in inflammatory diseases.